Hubungan Faktor Kesehatan Lingkungan dengan Tinggi Rendahnya House Index (HI) di Desa Endemis dan Desa Bebas Demam Berdarah Dengue di Kota Semarang - Nurjazuli, Nurjazuli; Ginanjar, Praba (Jurnal Kesehatan Lingkungan Indonesia, 2002)
Dengue Haemorhargic Fever was still one of the serious health problem, especially in urban area. Semarang is one of the endemic district area in central of Java with the highest incidence rate. In 1994, It had 15,24 per 10.000 population in incidence rate and 27,5 % of the house index. Three years after (1997), 124  among 177 villages ( 70,1 % ) in Semarang to be endemic. These situations  may be correlated to environmental factors i.e. water supply system and the housing condition. The objectives of this study was to know the relationship between the environmental health factor with the house index in free and endemic village of dengue haemorhargic fever ( DHF ). Cross-sectional design was used in this study. Samples were taken with stratified  random sampling  from two villages ( 75 from free area of DHF and 75 from endemic area. The study took place in Bendan Duwur ( as endemic area ) and Ngijo ( as free area )  of DHF. The collected data would be analyzed using Chi-Square techniques at 0,05 level of significance. The results of this study, there was no relationship between environmental health factor and the house index. On the other hand, trere was relationship between the cleaning of breeding places of mosquitoes and the house index ( p = 0,013 ). Keywords:  Environmental Health Factor, House Index, Semarang,1999